Inspiratory Muscle Weakness is Related to Poor Short-Term Outcomes for Heart Transplantation - Isis Begot (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Introduction: In heart transplantation (HT) recipients, several factors are critical to promptly adopting appropriate rehabilitation strategies and may be important to predict outcomes way after surgery. This study aimed to determine preoperative patient-related risk factors that could adversely affect the postoperative clinical course of patients undergoing HT. Methods: Twenty-one hospitalized patients with heart failure undergoing HT were evaluated according to respiratory muscle strength and functional capacity before HT. Mechanical ventilation (MV) time, reintubation rate, and intensive care unit (ICU) length of stay were recorded, and assessed postoperatively. Results: Inspiratory muscle strength as absolute and percentpredicted values were strongly correlated with MV time (r=-0.61 and r=-0.70, respectively, at P<0.001). Concerning ICU length of stay, only maximal inspiratory pressure (MIP) absolute and percent-predicted values were significantly associated. The absolute |MIP| was significantly negatively correlated with ICU length of stay (r=-0.58 at P=0.006) and the percent-predicted MIP was also significantly negatively correlated with ICU length of stay (r=-0.68 at P=0.0007). No associations were observed between preoperative functional capacity, age, sex, and clinical characteristics and MV time and ICU length of stay in the cohort included in this study. Patients with respiratory muscle weakness had a higher prevalence of prolonged MV, reintubation, and delayed ICU length of stay. Conclusion: An impairment of preoperative MIP was associated with poorer short-term outcomes following HT. As such, inspiratory muscle strength is an important clinical preoperative marker in patients undergoing HT.